2022
DOI: 10.1038/s41598-022-05351-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of actual exposure to facial sheet mask preceding its risk assessment

Abstract: The present study aimed to reveal the amount per application of facial sheet masks and its influencing factors in Chinese population to form the base for an accurate exposure assessment. A total of 175 healthy subjects aged 18 years or older were recruited and divided into two subgroups: one group of 35 subjects were asked to apply same mask for 5, 10, 15, 20, 25, and 30 min respectively, and the other 140 subjects were instructed to apply one of four types of facial sheet masks presented in the market for 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
(11 reference statements)
0
7
0
1
Order By: Relevance
“…Bamboo activated carbon base, used in the mask, can strengthen oil adsorption on skin surface. 23 As a result, adding the mask could improve acne severity (−0.39 ± 0.08 vs. −0.12 ± 0.09, p = 0.026) and closed comedones on the face (−6.56 ± 0.39 vs. −5.19 ± 0.44, p = 0.022) more significantly than simply using serum. Furthermore, the study mask contained nicotinamide, which has been shown to improve PIH intensity and skin tone evenness.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Bamboo activated carbon base, used in the mask, can strengthen oil adsorption on skin surface. 23 As a result, adding the mask could improve acne severity (−0.39 ± 0.08 vs. −0.12 ± 0.09, p = 0.026) and closed comedones on the face (−6.56 ± 0.39 vs. −5.19 ± 0.44, p = 0.022) more significantly than simply using serum. Furthermore, the study mask contained nicotinamide, which has been shown to improve PIH intensity and skin tone evenness.…”
Section: Discussionmentioning
confidence: 97%
“…Both the serum and mask contained SA, which may enhance the efficacy of dissolving oil and dredging pores. Bamboo activated carbon base, used in the mask, can strengthen oil adsorption on skin surface 23 . As a result, adding the mask could improve acne severity (−0.39 ± 0.08 vs. −0.12 ± 0.09, p = 0.026) and closed comedones on the face (−6.56 ± 0.39 vs. −5.19 ± 0.44, p = 0.022) more significantly than simply using serum.…”
Section: Discussionmentioning
confidence: 99%
“…[11] To achieve a long shelf life, preservatives and other additives are usually included in the facial mask, frequently resulting in various skin problems, including facial irritation and dermatitis. [3,6,12] Fabrication of solid facial masks is a practical strategy to eliminate additives. For example, hyaluronic acid (HA), crude huangshui polysaccharide, and polyvinyl alcohol were mixed and electrospun into a solid facial mask, which can be stored without preservatives and exhibited simultaneous excellent moisture retention and oxidation resistance.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1,2 ] According to the statistics of the mask sales platform during 2021–2022, the facial mask market is as high as 43.18 billion RMB in China, which will exceed 64.5 billion RMB in 2024. [ 3 ] The main principle of a facial mask is to create a closed space with skin, supple skin with water and active ingredients, keep skin moist, remove sebum from the skin, and maintain proper skin health. [ 4 ] Nowadays, the primary function of facial masks includes hydration, skin repair, whitening, blemishing, oil control, acne removal, and anti‐aging.…”
Section: Introductionmentioning
confidence: 99%
“…The skincare market is vast and encompasses a wide range of applications, from therapeutic treatments to beauty enhancements. , However, the environmental pollution resulting from excessive plastic packaging, the consumption of fossil fuels, and the incorporation of environmentally unfriendly additives is a matter of serious concern. In the sheet mask market, despite the availability of environmentally sustainable materials such as cellulose, silk, and other eco-friendly sheet mask substrates, a significant portion of sheet masks still consist of nonbiodegradable nonwoven fabrics made from petrochemical-based plastics. Additionally, traditional wet sheet masks face challenges like ingredient degradation, environmental impact, the use of preservatives, and a limited shelf life necessitating wet storage, which inevitably leads to the use of plastic and metal packaging. , Also, traditional wet masks commonly use hydrophilic (HL) fabrics to ensure sufficient nutrient absorption. , These fabrics can lead to moisture evaporation or reverse moisture absorption from the skin surface, negatively impacting the product’s effectiveness.…”
Section: Introductionmentioning
confidence: 99%